Agroturismo en la Finca Privilegio del cantón Olmedo, provincia de Loja - Robles Armijos, Katherine Mercedes (2024)
Agrotourism in recent years has proven to be an option for diversification of agricultural, agro-industrial, artisanal or gastronomic activities, allowing the reactivation of rural areas and facilitating tourists to have interactive experiences with the rural world. The general objective of this research is to develop an agro-tourism proposal for the Finca Privilegio in the Olmedo canton, Loja province, supported by two specific objectives: Evaluate the agro-tourism potential using the manual for the design and operation of agro-tourism products, which worked in five phases: characterization of the territory, CICATUR/OEA cards for the inventory of tourist attractions, interviews with key informants to identify the tourism offer, a survey to determine potential demand, and the development of the SWOT and Strategy Matrix. The second specific objective was to formulate the design of tourism products for Finca Privilegio, through three steps: review of the basic principles for identifying tourism products, design of the tourism product portfolio, and organization and management of tourism products. Following the development of the SWOT, four key strategies were obtained for the development of the second objective. Among the results obtained, it was determined that Finca Privilegio has tourism resources, agrotourism activities and the ideal space for the construction of the infrastructure needed to strengthen and promote the development of agrotourism.